A 7-mg miniature catalytic-combustion engine for millimeter-scale robotic actuation - Maimani, Fares; Calderón, Ariel A.; Yang, Xiufeng; Rigo, Alberto; Ge, Joey Z.; Pérez-Arancibia, Néstor O. (Sensors and actuators. A. Physical., 2022)
[Display omitted] •7-Milligram miniature engine using shape-memory alloy wires coated with platinum.•Engine operates at 6 Hz, lifts 650 times its weight, generates 39.5 μW average power,•Chemical fuels and catalytic combustion for energy dense microrobotic actuation.•Thermal and dynamic modeling predict engine frequency and actuation output.•Fast custom-built fuel delivery system demonstrates engine's applicability. Microrobots at the subcentimeter scale have the potential to perform useful complex tasks if they were to become energy independent and could operate autonomously. The vast majority of current microrobotic systems lack the ability to carry sufficient onboard power to operate and, therefore, remain tethered to stationary sources of energy in laboratory environments. Recent published work demonstrated that chemical fuels can react under feedback control on the surfaces of tensioned shape-memory alloy (SMA) nickel-titanium (NiTi) wires coated with platinum (Pt) catalyst. Combining catalytic combustion of fuels with high energy densities with the high work densities of SMA wires is a promising approach to provide onboard power to microrobots. In this article, we present a novel 7-mg SMA-based miniature catalytic-combustion engine for millimeter-scale robotic actuation that is composed of a looped NiTi-Pt composite wire with a core diameter of 38 μm and a flat carbon-fiber beam with a length of 13 mm. This beam acts as a leaf spring during operation. The proposed design of the engine has a flat and narrow geometry, functions according to a periodic-unimorph actuation mode, and can operate at frequencies as high as 6 Hz and lift 650 times its own weight while functioning at 1 Hz, thus producing 39.5 μW of average power in the process. For the purposes of design and analysis, we derived a model of the heat transfer processes involved during actuation, which combined with a Preisach-model-based description of the SMA wire dynamics, enabled us to numerically simulate the response of the miniature system, and thus predict its performance in terms of frequency and actuation output. The suitability for microrobotics and functionality of the proposed approach is demonstrated through experimental results using a custom-built fast-response high-precision system of fuel delivery.